High ureum and creatinine level in 18-year-old male: first diagnosed with chronic kidney disease - I Made Dwi Payana; Ni Nengah Tuti Arianthi; I Made Sila Darmana (Intisari Sains Medis, 2020)
Introduction: Chronic Kidney Disease (CKD) needs to be rapidly diagnosed and treated correctly. The classic patient characteristics were anaemia, hypertension, oedema, albuminuria and decrease of renal function. In a few cases, CKD can occur in an atypical patient, such as in young age.Case report: We herein report a case of an 18-year-old male with Renal failure. The patient noted to be anaemic, fatigue, oedema, hypertension which is consisted of features typical of Chronic kidney disease. Laboratory examination revealed low haemoglobin level, high ureum and creatinin, and albuminuria. The patient underwent hemodialysis and was given Packed Red Cell (PRC) transfusions.Conclusion: CKD had to be suspected of all age so that it can be rapidly diagnosed and treated correctly.